(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The purpose of the study was to determine the extent of staphylococcal contamination in various environmental sites and to characterize the isolates by antibiotic susceptibility. Methods: A cross-sectional study was conducted and 123 samples were collected from 9 different sites around Kathmandu valley. Isolation of S. aureus was done through cultural and biochemical analysis. Kirby-Bauer disc diffusion test was employed to test the susceptibility of isolates to antibiotics. Results: A total of 25 S. aureus (20.33%) were isolated; among which 12 isolates exhibited methicillin resistance i.e. 48% (MRSA) and 13 isolates were methicillin susceptible, 52% (MSSA). Similarly, 53 Coagulase Negative Staphylococci (CoNS) were isolated; among which 17(32.07%) were resistant to methicillin. The antibiotic resistance patterns of MRSA were reported as: erythromycin(n=2;16.6%.), clindamycin (n=2;16.6%), cotrimoxazole (n=2;16.6%), ciprofloxacin (n=2;16.6%) and gentamicin (n = 1;8.3%). MRCoNS showed high resistance to erythromycin (n=6; 35.2%), followed by co-trimoxazole (n=4; 23.5%), novobiocin (n=4; 23.5%) and ciprofloxacin (n=3; 17.6%). All MRSA and MRCoNS isolates were susceptible to linezolid and clindamycin. Conclusion: This study reports relatively high prevalence of MRSA on environmental surfaces, pre-dominating in areas having heavy crowds. There may be a likely connection between humans and the environment to share MRSA and MSSA.